Analisis Daya Tahan Cardiovascular (Vo2max) Pada Pemain Futsal Putri Ekstrakurikuler SMAN 6 Kepahiang - Irfan, Aldi; Apriansyah, Dolly; Anggara, Deffri (Educative Sportive, 2024)
This study aims to describe how Cardiovascular Endurance (Vo2max) in Female Futsal Players Extracurricular SMAN 6 Kepahiang. The population in this study were all players who participated in extracurricular activities and the sample in this study consisted of 17 female futsal players with sampling techniques using total sampling techniques. This type of Quantitative Descriptive research uses test and measurement methods and documentation. The results showed that the level of cardiovascular endurance of female futsal extracurricular participants at SMAN 6 Kepahiang was in the sufficient category. With the acquisition of the results of VO2Max players in each category, it shows that the level of cardiovascular endurance of female futsal extracurricular participants of SMAN 6 Kepahiang, no one has obtained a very good category and there are 5 players with a percentage (29%) in the good category, 9 players with a percentage (53%) in the sufficient category, 1 player with a percentage (6%) in the deficient category, 2 players with a percentage (12%) in the very deficient category.